2022
DOI: 10.18502/ajmb.v14i3.9830
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Durability of SARS-CoV-2-specific IgG and IgM Antibodies in Recovered COVID-19 Patients: A Prospective Study

Abstract: Background: Evidence on seroconversion profile of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected patients is limited. We mainly aimed to evaluate seroconversion and persistence of virus-specific antibodies in patients infected by coronavirus disease 2019 (COVID-19). Methods: This prospective study was conducted on 118 patients with COVID-19 presentations admitted to three hospitals in Iran and recovered from the disease, during April and May 2020. Presence of COVID-19 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Zamani et al [ 16 ] studied the kinetics of seroconversion in 118 hospitalized patients with COVID-19 (Table 1 ). The authors demonstrated the kinetics of seroconversion in COVID-19 patients, and showed that 83.5% of IgM and 36.8% of IgG patients who were originally positive were found to be negative within 3 mo after the onset of symptoms.…”
Section: Dynamic Changes In Sars-cov-2 Specic Antibodiesmentioning
confidence: 99%
“…Zamani et al [ 16 ] studied the kinetics of seroconversion in 118 hospitalized patients with COVID-19 (Table 1 ). The authors demonstrated the kinetics of seroconversion in COVID-19 patients, and showed that 83.5% of IgM and 36.8% of IgG patients who were originally positive were found to be negative within 3 mo after the onset of symptoms.…”
Section: Dynamic Changes In Sars-cov-2 Specic Antibodiesmentioning
confidence: 99%